Incorporate your business : in any state - Spadaccini, Michael, 1964- (Irvine, CA : Entrepreneur Press, 2007)
An overview of business organizations -- Information for all businesses -- The features of corporations -- The 13 steps to incorporating -- Operating your corporation -- Suing and being sued as a corporation -- Managing and maximizing liability protection.